2021
DOI: 10.1007/s00384-021-03841-w
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open rectal resection: a 1:2 propensity score–matched analysis of oncological adequateness, short- and long-term outcomes

Abstract: Background Laparoscopic resections for rectal cancer are routinely performed in high-volume centres. Despite short-term advantages have been demonstrated, the oncological outcomes are still debated. The aim of this study was to compare the oncological adequateness of the surgical specimen and the long-term outcomes between open (ORR) and laparoscopic (LRR) rectal resections. Methods Patients undergoing laparoscopic or open rectal resections from January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…When the HRs and 95% CI were not provided in the studies, two authors (AC and EMM), following well-established methodologies, extracted data from Kaplan-Meier (KM) curves with GraphClick software 3.0 for Mac (Arizona-Software, Phoenix, AZ, USA) and estimated the HRs using an on-line calculator (https://www.gigacalculator.com/calculators/hazard-ratio-calculator.php, accessed on 15 April 2022). The method was validated with a blind approach by correlating the data extracted from our previously published KM curves [28][29][30] with the original data or by comparing the HR of the same study reported in other meta-analyses [31]. The HR was converted to logHR and SE with variance.…”
Section: Discussionmentioning
confidence: 99%
“…When the HRs and 95% CI were not provided in the studies, two authors (AC and EMM), following well-established methodologies, extracted data from Kaplan-Meier (KM) curves with GraphClick software 3.0 for Mac (Arizona-Software, Phoenix, AZ, USA) and estimated the HRs using an on-line calculator (https://www.gigacalculator.com/calculators/hazard-ratio-calculator.php, accessed on 15 April 2022). The method was validated with a blind approach by correlating the data extracted from our previously published KM curves [28][29][30] with the original data or by comparing the HR of the same study reported in other meta-analyses [31]. The HR was converted to logHR and SE with variance.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal malignancies have been commonly dealt with by laparoscopic methods in most parts of the world as more and more surgeons have been trained to perform minimally invasive surgery. 12,13 Several factors could be incorporated into the plan to determine the best method for surgery. 14 However, in the case of malignancies, the better immediate histopathological outcome remains the most important factor.…”
Section: Discussionmentioning
confidence: 99%
“…A minimally invasive approach is nowadays considered the treatment of choice of colorectal malignancies, being associated with low postoperative comorbidities and short length of hospital stay [ 20 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%